1971
DOI: 10.1037/h0032251
|View full text |Cite
|
Sign up to set email alerts
|

Psychological thrillers: Psychology books students read when given freedom of choice.

Abstract: SYCHOLOGY as a topic of general interest is possibly more popular with the general public than is psychology as an academic subject-field with college students. Furthermore, the content of the general interest psychology is probably quite different from the content of a college course. What is there about the "good" psychology of the classroom that is less enticing than the "inferior" popular brand?Is it possible that academic psychology is designed solely for potential professional psychologists and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Several articles (e.g., LeUnes, 1974;McCollom, 1971) in recent years have reported on supplementary reading materials that qualify as "psychological thrillers"-books that students find interesting and thoughtprovoking. It is perhaps even more important that teachersof psychology share their knowledge of such psychological thrillers in other media, such as film, that are more difficult for an individual instructor to review.…”
Section: Developmental Psychopathology Learning and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles (e.g., LeUnes, 1974;McCollom, 1971) in recent years have reported on supplementary reading materials that qualify as "psychological thrillers"-books that students find interesting and thoughtprovoking. It is perhaps even more important that teachersof psychology share their knowledge of such psychological thrillers in other media, such as film, that are more difficult for an individual instructor to review.…”
Section: Developmental Psychopathology Learning and Behaviormentioning
confidence: 99%
“…Evaluations for the course textbook (Mussen, Conger, & Kagan, 1974), which is one of the most widely used texts in child and developmental psychology courses, are included as a basis for comparison. It was found that all of the films listed here also had a mean rating more favorable than most supplementary reading books and reprints used-except for Axline's (1964) Dibs In Search of Self, which is perhaps the most popular book among college psychology students across the country (LeUnes, 1974;McCollom, 1971McCollom, , 1975. Among the writer's students at UCLA, Dibs has also been the most popular reading (mean rating 7.96), yet three of the recommended films closely match even this perennial literary favorite.…”
mentioning
confidence: 89%
“…The technique requires little faculty time and can be readily adapted to other areas. McCollom (1971) reported on the use of "psychological thrillers" to get undergraduates to read books related to psychology. More recently Le Unes (1974) reported on the value of the technique for graduate students.…”
Section: Thrillers Among the Journals: A Technique To Increase Gradua...mentioning
confidence: 99%
“…The author will often describe the activities of an entire research project, generating a global perspective of many thingsthat do not appear in the professional journals. A distinct advantage of teaching the history of psychology this way can be identified in a study by McCollum (1971) where students revealed that they rated one autobiography high on the list of books they wanted to read in psychology courses. Students enjoy reading about others, and in many ways this method also supplies a need for the student who wishes to pursue a career in psychology.…”
mentioning
confidence: 96%